Validity of integral calculus textbook with indonesian cultural and religious values - Marhayati; Fa'ani, Arini Mayan; Faridah, Siti (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
Students' difficulties in understanding Integral Calculus material is one of the factors of low learning outcomes. This research aims to develop an Integral Calculus textbook with nuances of Indonesian culture and religious moderation in accordance with the curriculum in the Tadris Mathematics Study Program at UIN Maulana Malik Ibrahim Malang. The type of research carried out is Research and Development (R&D) with ADDIE (Analysis, Design, Develop, Implementation, and Evaluation) model is used. The instrument used in this research is an expert validation sheet consisting of material validation, learning, design, and moderation religious. The results of expert validation regarding material, learning, design, and religious moderation with percentages of 91.07%; 93,75%; 85% and 90%, respectively, the textbooks are declared valid 86% met the very positive criteria. Based on the validity test and positive student responses, it was concluded that the textbook was valid so it could be used in teaching Integral Calculus.